The Importance of Veterinary Policy in Preventing the Emergence and Re-Emergence of Zoonotic Disease: Examining the Case of Human African Trypanosomiasis in Uganda - Okello, Anna L.; Welburn, Susan C. (Frontiers in Public Health, 2014)
Rapid changes in human behaviour, resource utilisation and other extrinsic environmental factors continue to threaten the current distribution of several endemic and neglected zoonoses worldwide. There are numerous examples of zoonotic diseases which have circulated within relatively localised geographical areas for some time, before emerging into new regions. Whilst the world’s focus is currently on the Ebola virus, another pertinent example is zoonotic Human African Trypanosomiasis, endemic to south and eastern Africa and spread via infected cattle. In recent years, the ongoing northwards spread of this disease in the country has posed a serious public health threat to the human population of Uganda, increasing the pressure on both individual families and government services to control the disease. Moreover, the emergence of Human African Trypanosomiasis into new areas of Uganda in recent years exemplifies the important role of veterinary policy in mitigating the severe human health and economic impacts of zoonotic disease. The systemic challenges surrounding the development and enforcement of veterinary policy described here highlight the necessity to address zoonoses control in broader health and development programmes.